Modified Valsalva manoeuvre to treat recurrent supraventricular tachycardia: description of the technique and its successful use in a patient with a previous near fatal complication of DC cardioversion. (8th July 2014) - Appelboam, Andrew; Gagg, James; Reuben, Adam
Abstract : Patients with attacks of re-entrant supraventricular tachycardia (SVT) frequently present to the emergency department (ED). The Valsalva manoeuvre (VM) is the most effective and safe vagal manoeuvre and advocated as the first-line treatment in stable patients but has a relatively low cardioversion success rate. Improving its efficacy would reduce patients' exposure to the side effects and complications of second-line treatments and has other potential benefits. We describe a modification to the VM, which is currently being studied, and present the case of a 23-year-old patient who was successfully treated with this modified VM after a previous near-fatal complication of direct current (DC) cardioversion.